Siemens Control System Simulator's Impact On Customers Plant Operation And Maintenance Performance - Phang, Audrey Yeng Ling (2006)
Power plant industries undergoing restructuring to achieve competitive advantage, this paper intends to investigate through interview and problem solving excercises to find out how the Siemens Control System simulator would be capable of playing the role as a decision support tool to assist in evaluating and improving plant operation and maintenance work performance, to achieve the ultimate aim of downtime reduction, higher availability and long term plant reliability.